2021
DOI: 10.2147/prbm.s335407
|View full text |Cite
|
Sign up to set email alerts
|

Peer Phubbing and Chinese College Students’ Smartphone Addiction During COVID-19 Pandemic: The Mediating Role of Boredom Proneness and the Moderating Role of Refusal Self-Efficacy

Abstract: Purpose: COVID-19 has had a huge impact on the physical behavior and mental health of people. Long-term and strict isolation policies are widely used to ensure social distancing, which may cause excessive smartphone use and increase the risk of smartphone addiction. Previous researchers have identified that some factors that affect smartphone addiction, but there was little research conducted during COVID-19 pandemic. The present study aims to examine the effect of peer phubbing on smartphone addiction, how bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 71 publications
(87 reference statements)
2
14
0
Order By: Relevance
“…The association between environmental risk factors and problem behaviors would be reduced by individual attributes such as regulatory emotional self-efficacy, in line with the "risk buffering hypothesis" (62)(63)(64). The hypothesis proposed that protective factors may mitigate the negative consequences of risk factors.…”
Section: The Moderating Role Of Regulatory Emotional Self-efficacymentioning
confidence: 81%
See 2 more Smart Citations
“…The association between environmental risk factors and problem behaviors would be reduced by individual attributes such as regulatory emotional self-efficacy, in line with the "risk buffering hypothesis" (62)(63)(64). The hypothesis proposed that protective factors may mitigate the negative consequences of risk factors.…”
Section: The Moderating Role Of Regulatory Emotional Self-efficacymentioning
confidence: 81%
“…During the epidemic, effects of the absence of specific drugs for COVID-19 and the reduction in social interaction due to keeping a social distance ( 4 ) predispose individuals to develop negative emotions ( 26 ). As epidemic prevention measures were strictly enforced, access to social interactions decreased and mobile phone use increased ( 64 ), with the consequently increased availability of mobile social media use ( 16 , 44 ). Through the use of social media, individuals were able to obtain positive social feedback and momentarily forget about negative emotions ( 21 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several studies have identified factors causing mobile phone addiction during the COVID-19 pandemic. For example, household financial decline due to COVID-19, peer phubbing, interpersonal alienation, loneliness, escape motivation, perceived stress, and social cynicism have been reported to be significant positive predictors of mobile phone addiction [23][24][25][26][27][28]. Kayis et al [10] conducted a questionnaire survey among 773 adults and determined that the fear of COVID-19 had a significant positive predictive effect on mobile phone addiction.…”
Section: Covid-19 Victimization Experience and Mobile Addictionmentioning
confidence: 99%
“…Peer relationships have a critical impact on adolescent mobile phone addiction [ 9 ]. Peer phubbing refers to the state that individuals feel ignored by peers because their peers pay more attention to mobile phones [ 11 ]. Peer phubbing is a typical manifestation of phubbing in peer interactions.…”
Section: Introductionmentioning
confidence: 99%